The current situation of Vietnamese enterprises’ digital transformation and solutions - Nguyen Nguyet Minh (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2023)
During the 4.0 Industrial Revolution, digital transformation is an inevitable trend, playing an important role in the economic growth of countries around the world, including Vietnam. This paper clarifies the digital transformation policies of the Vietnamese Government, and evaluates the current situation, opportunities and challenges of Vietnamese firms’ digital transformation process. Research results show that although Vietnamese firms have enormous demand for digital transformation, most are in the early stages of the digital transformation process and cannot master the technology. Intra-firm digital transformation activities are performed incoherently with a lack of synchronization. The main barriers to Vietnamese firms’ digital transformation process may include limited resources, lack of qualified human resources and slow-changing mindset. Finally, solutions and policy recommendations are also discussed by the author in this study. Code: 23101101